Exploring the Mysteries of Shooting Stars: From Cosmic Phenomenon to Cultural Significance - Belay Sitotaw Goshu; Muhammad Ridwan (Lakhomi Journal Scientific Journal of Culture, 2024)
We investigate the intriguing phenomenon of shooting stars, looking at how they behave at greater altitudes and how they eventually disintegrate. Shooting stars fly through the atmosphere and change, shedding mass as they ignite and become thermal energy. This process ends with their disappearance, having traveled around 45.34 kilometers. We examine their journey using displacement vectors and find a pattern that may be expressed as r=33.5i−15.0j. In addition, the study of the probability distribution of broken mass, providing insights into the complex dynamics of meteorites. The results show that meteorites can be classified into some groups, including L to L5, L6, and H to H4, H6, and CM2. These groups have different compositions and percentages. Notably, our study finds that failed meteorites are more common in equatorial locations, indicating the presence of underlying environmental influences. Our data reveals notable variations in meteorite classifications through time when looking at temporal trends. Peak events of some classes, like H, L, and LL, align with particular periods, providing information about the temporal dynamics of astronomical phenomena. Because historical accounts frequently conflate celestial phenomena with cultural and religious beliefs, these data raise questions about how culture and religion impact our understanding of these cosmic events. Our study highlights the multifaceted character of celestial occurrences by fusing scientific investigation with cultural and religious viewpoints. This encourages more research at the nexus of science, culture, and spirituality.